Self-assembled dextrin nanogel as curcumin delivery system - Gonçalves, Catarina (2012)
Curcumin is a natural polyphenol with anti-oxidative, anti-inflammatory and anti-cancer properties. Its therapeutic potential is substantially hindered by the rather low water solubility and bioavailability, hence the need for suitable carriers. In this study, we show that self-assembled nanogels obtained from hydrophobically modified dextrin are effec-tive curcumin nanocarriers. The stability and loading efficiency of curcumin-loaded nanogel depends on the nano-gel/curcumin ratio. Higher stability of the formulation is achieved in water than in PBS buffer, as evaluated by dynamic light scattering and fluorescence measurements. The in vitro release profile, using sink conditions, indicates that dextrin nanogel may perform as a suitable carrier for the controlled release of curcumin. Biological activity of curcumin-loaded nanogel in HeLa cell cultures was assessed using the MTS assay.